Assessing Community Needs to Combat the Opioid Epidemic in Washtenaw County, Michigan. Issue 3 (May 2021) - Marquez, Juan Luis; Loveluck, Jimena; Marshall, Jessie Kimbrough; Power, Laura
Abstract : A needs assessment was performed to inform the strategic plan of the Washtenaw Health Initiative Opioid Project (WHI-OP). A Health Resources & Services Administration–funded preventive medicine resident supported this work by conducting and analyzing surveys and face-to-face interviews. Surveys were distributed to community organizations involved in opioid prevention and treatment and medical providers in the major health care systems. Individual interviews were conducted with key stakeholders. Overall, the top 5 needs identified were (1) pain management treatment options, (2) addressing provider stigma, (3) community education of opioids and substance abuse, (4) access to substance use disorder treatment, and (5) better guidelines to manage care for patients with substance use disorder, given the evolving Michigan prescription laws. The findings served as a foundation for a new strategic plan for the WHI-OP. The needs assessment was accomplished through the work of the preventive medicine resident in close collaboration with the WHI-OP and the Washtenaw County Health Department. Abstract : Supplemental Digital Content is Available in the Text.